A numerical experiment on hail forecast: Hailstorms on 17 March 2020 in western North Vietnam - Doan Manh, Duy; Nguyen Minh, Truong; Nguyen Vinh, Thu; Hoang Thi Thanh, Thuat (Vietnam Journal of Earth Sciences, 2024)
This study utilized the Weather Research and Forecast (WRF) model to forecast hail induced by the hailstorms on 17 March 2020 in western North Vietnam, using two microphysical schemes: the Thompson and Morrison schemes. Assessment of the WRF skill in predicting hail coverage and intensity was done for two predicted indices, namely UH (Updraft Helicity) and CTG (Column Total Integrated Graupel). Two predicted variables are DTh (hail diameter given by WRF using the Thompson Hail Algorithm) and DHc (hail diameter given by the HAILCAST submodel in WRF). The predicted hail coverage and intensity were compared with the products given by the Pha Din radar's Hail Size Discrimination Algorithm (HSDA) for three categories: small, large, and giant hail size. Using the Morrison scheme, the WRF model indicates that the hail-coverage forecast skills of UH, CTG, and DHc are highest, with an insignificant difference at the horizontal scale larger than 60 km. However, the DHc variable given by the Morrison scheme provides the most successful forecast for both hail size and coverage compared with the HSDA products and field reports. This is because HAILCAST considers kinematic and microphysical processes to predict maximum hail size at the surface. The predicted hailstorms could occur in environments with moderate convective available potential energy but require robust moisture flux convergence over high mountains.